2015
DOI: 10.7567/jjap.54.07jc06
|View full text |Cite
|
Sign up to set email alerts
|

Non-doped and doped Mg stannide films on Si(111) substrates: Formation, optical, and electrical properties

Abstract: Thin (45-50 nm) non-doped and doped (by Sb and Al) polycrystalline Mg stannide films consisting mainly of Mg 2 Sn semiconductor phase and containing small quantity of Mg 2 Si phase have been grown by multiple layer deposition at room temperature and single step annealing at 150 °C of the (Sn-Mg) bi-layers on Si(111) n-type wafers with 7.5 Ω&cm resistivity. Optical spectroscopy data have shown that the grown Mg stannide films is a semiconductor with direct band gap of 0.17 + 0.03 eV, with second and third direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…AFM has measured root-mean square roughness of 2.3 -3.5 nm that indicates a continuous film formation. Far infrared (FIR) properties of grown Mg2Sn films have also proved the formation of Mg stannide with small quantity of Mg silicide [23]. The results presented in [23] were measured short after removing the samples from the growth chamber, while the results presented in this work characterize samples about 6 -12 month after sample preparations.…”
Section: Sample Preparation and In Situ Experimentsmentioning
confidence: 79%
See 2 more Smart Citations
“…AFM has measured root-mean square roughness of 2.3 -3.5 nm that indicates a continuous film formation. Far infrared (FIR) properties of grown Mg2Sn films have also proved the formation of Mg stannide with small quantity of Mg silicide [23]. The results presented in [23] were measured short after removing the samples from the growth chamber, while the results presented in this work characterize samples about 6 -12 month after sample preparations.…”
Section: Sample Preparation and In Situ Experimentsmentioning
confidence: 79%
“…45 ·cm p-type boron doped Si(111) wafer fragments were used as substrate. The details of Mg2Sn solid phase epitaxy (SPE) growth was described in [23]. The …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known thatAg, Ga and Cu atoms act as donor impuritiesfor Mg 2 X (X=Si, Sn, Ge) compounds 8,9 . Recently it was found that in the nondoped Mg 2 Sn polycrystalline films grown by solid phase epitaxy from Sn-Mg multilayers on Si (111) n-type substrate has a complex conductivity and carrier mobility behavior, which is explained by change of hole conductivity at low temperature (100-230 K) on the electron conductivity at temperatures 250-420 K due to beginning of intrinsic conductivity in Mg 2 Sn film 10 . However Mg 2 Si x Sn 1-x ternary alloy films have not been grown on atomically clean Si(111) surface and have not been studied their structure and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of embedding of Mg and Ca silicide and stannide nanocrystals (5-20 nm) in the polycrystalline and amorphous silicon matrix the crystalline structure with arbitrary orientation relatively a silicon matrix is observed. By methods of transmittance and reflectance optical spectroscopy it was established that in the reflectance spectrum the appreciable peaks at energies up to 2.5 eV are formed at increasing of embedded NCs layer quantities [8,9], but in the Raman spectra the peaks correlated with ones of silicides and stannides are observed [10,11]. In MNHS with seven embedded EFeSi2 NCs and thin silicon interlayers (10-12 nm) the electroluminescence with 25 micro watt power emission in the wavelength range of 1500-1550 nm at 300 K was firstly observed that corresponds to suppression of non-radiative recombination centers, and also to appearance of the quantum Stark effect and formation of excitons with binding energy more than 3/2kT.…”
mentioning
confidence: 99%